Import liberalization and employment : the effects of unilateral reductions in United States import barriers - Salant, Walter S.; Vaccara, Beatrice N. (Washington : Brookings Institution, 1961)
This study is intended as a contribution to our knowledge about one of these short-run effects: the effects on the level of employment in the United States that might be expected if the United States were to make a unilateral reduction in its tariff or other protective barriers against imports.
Bibliographical footnotes.
osc 19/07/2018
Loans
Keywords: Labor supply; United States